1994
DOI: 10.1002/ijc.2910570315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urinary trypsin inhibitor on the invasion of reconstituted basement membranes by ovarian cancer cells

Abstract: Using the human ovarian cancer cell line HOC-1, we investigated the effects of urinary trypsin inhibitor (UTI) purified from human urine and its related synthetic peptides on the invasive potential of cancer cells in an in vitro assay. Invasiveness of tumor cells was determined using a modified Boyden chamber and a reconstituted basement membrane Matrigel. Three peptides (peptide 1, peptide 2, and peptide 3), representing sequences within UTI, were synthesized. HOC-1 cells showed detectable and reproducible le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The role of the u-PA system in cell invasion has been investigated in several different in vitro assays, including assays with invasion through an isolated human amniotic membrane (Mignatti et al, 1986;Kirchheimer and Remold, 1989;Tsuboi and Rifkin, 1990;Brückner et al, 1992), into Matrigel (Reich et al, 1988;Cajot et al, 1989;Schlechte et al, 1990;Tsuboi and Rifkin, 1990;Hollas et al, 1991;Meissauer et al, 1991;Clayman et al, 1993;Crowley et al, 1993;Karikó et al, 1993;Mohanam et al, 1993;Rao et al, 1993;Kobayashi et al, 1993bKobayashi et al, , 1994aKobayashi et al, , c, d, e, 1995Stahl and Mueller, 1994;Wilhelm et al, 1994;Jarrard et al, 1995;Liu et al, 1995;Quattrone et al, 1995;Soff et al, 1995;Wilhelm et al, 1995;Bianchi et al, 1996;Holst-Hansen et al, 1996;Luparello and Del Rosso, 1996;Min et al, 1996;Xing and Rabbani, 1996) and into a fibrin gel (Montesano et al, 1987Kramer et al, 1994). The main conclusions to emerge from the use of these assays are as follows:…”
Section: In Vitro Assays Of Cell Invasionmentioning
confidence: 99%
“…The role of the u-PA system in cell invasion has been investigated in several different in vitro assays, including assays with invasion through an isolated human amniotic membrane (Mignatti et al, 1986;Kirchheimer and Remold, 1989;Tsuboi and Rifkin, 1990;Brückner et al, 1992), into Matrigel (Reich et al, 1988;Cajot et al, 1989;Schlechte et al, 1990;Tsuboi and Rifkin, 1990;Hollas et al, 1991;Meissauer et al, 1991;Clayman et al, 1993;Crowley et al, 1993;Karikó et al, 1993;Mohanam et al, 1993;Rao et al, 1993;Kobayashi et al, 1993bKobayashi et al, , 1994aKobayashi et al, , c, d, e, 1995Stahl and Mueller, 1994;Wilhelm et al, 1994;Jarrard et al, 1995;Liu et al, 1995;Quattrone et al, 1995;Soff et al, 1995;Wilhelm et al, 1995;Bianchi et al, 1996;Holst-Hansen et al, 1996;Luparello and Del Rosso, 1996;Min et al, 1996;Xing and Rabbani, 1996) and into a fibrin gel (Montesano et al, 1987Kramer et al, 1994). The main conclusions to emerge from the use of these assays are as follows:…”
Section: In Vitro Assays Of Cell Invasionmentioning
confidence: 99%
“…Several protease inhibitors, such as TIMPs (tissue inhibitor of metalloproteases), PAI-I and PAI-2 (plasminogen activator inhibitor type 1 and type 2), and urinary trypsin inhibitor have been reported to possess the ability to inhibit cell growth and cell invasion of carcinoma cells in vitro (Baker et al, 1990;Cajot et al, 1990;Albini et al, 1991;Declerck et al, 1992;Kennedy, 1994;Kobayashi et al, 1994Kobayashi et al, , 1995. Recently, transfection of maspin, which is a newly purified seine protease inhibitor, has been reported to reduce the malignancy of breast cancer cells (Zou et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Several proteases produced by the cancer cell itself have been reported to be associated with cancer invasion and metastasis (Liotta et al, 1980(Liotta et al, , 1986Wooley, 1984;Nakajima et al, 1987;Reich et al, 1988;Basset et al, 1990). Also several kinds of specific inhibitors of such proteases have been shown to inhibit cancer invasion and metastasis (Baker et al, 1990;Cajot et al, 1990;Albini et al, 1991;Declerck et al, 1992;Kennedy, 1994;Kobayashi et al, 1994Kobayashi et al, , 1995. Hence, the protease inhibitors could be considered to possess the potential to be a useful tool for the development of a new therapeutic method against cancer.…”
mentioning
confidence: 99%
“…16 The ITI-L chain mRNA encodes 2 tandemly arranged proteins that separate after proteolytic cleavage: the ␣ 1 -microglobulin (␣ 1 m) that belongs to the lipocalin superfamily 17 and the bikunin that contains 2 Kunitz inhibitory domains responsible for the protease inhibitory activity of ITI molecules. 18 Different studies have suggested a potential antimetastatic effect of bikunin: (i) it inhibits in vitro tumor cell receptor-bound plasmin 19 and the invasiveness of malignant cells; 20,21 and (ii) injections of human purified bikunin efficiently reduced the number of metastases produced by the murine 3LL cell line. 22 We have therefore analyzed in the present study the antimetastatic effect of the different ITI chains using a model of fluorescent spontaneous lung metastases.…”
mentioning
confidence: 99%